Assessing the validity and reliability of creative thinking skills module in a pilot study on engineering undergraduate in Malaysia - Chua, Yaw Long; Balakrishnan, Balamuralithara; Chai, Voon Chiet; Koh, Yit Yan (Asian Journal of Assessment in Teaching and Learning, 2020)
This research paper presents the outcome of a research conducted to assess and determine the Validity and Reliability coefficient of Creative Thinking Skills for Conceptual Engineering Design Module administered to engineering undergraduates at a private institution of higher learning. The Creative Thinking Skills Module features few proposed creative thinking tools such as Brain Sketching, Mind Maps and Morphological Analysis. The validity consists of module content validity, and session and activity validity, evaluated by a group of five experts. The Cronbach Alpha value was determined through conducting a pilot study in a local private university where mechanical engineering undergraduate underwent the module workshop and activity. Questionnaires were given to respective experts and students respondents to measure the validity and reliability level of the module, sessions and activities.